2006
DOI: 10.1086/505996
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II and Aldosterone Increase with Fasting in Breeding Adult Male Northern Elephant Seals (Mirounga angustirostris)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press ABSTRACTThe renin-angiotensin-aldosterone system (RAAS) appears to contribute significantly to osmoregulation of fasting northern elephant sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…This suggests that potential lipolytic benefits of elevations in cortisol [44] are secondary to other impacts on metabolism, including protein sparing. In contrast, aldosterone concentrations increased across the fast [45], which may support the hypothesis that aldosterone is an important factor in the stress response (in this case, prolonged nutrient deprivation).…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…This suggests that potential lipolytic benefits of elevations in cortisol [44] are secondary to other impacts on metabolism, including protein sparing. In contrast, aldosterone concentrations increased across the fast [45], which may support the hypothesis that aldosterone is an important factor in the stress response (in this case, prolonged nutrient deprivation).…”
Section: Introductionsupporting
confidence: 69%
“…Aldosterone response to ACTH was highest during late breeding when baseline aldosterone levels are highest. This suggests that pituitary stimulation may contribute independently to the strong upregulation of the RAS system seen across fasting [45]. The elevation of aldosterone had no significant effect on the electrolytes Na+ and K +.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The regulation of aldosterone release by the HPA axis may reflect the need to alter kidney perfusion and lung perfusion during diving, inhibiting typical RAS regulation (Atkinson et al, 2015). In contrast to the juveniles in the current study, aldosterone concentrations increased across the breeding fast in adult male elephant seals (Champagne et al, 2006;Ortiz et al, 2006) in association with RAS activation suggesting that this hormone may be under dual regulation by the HPA axis and RAS.…”
Section: Discussionmentioning
confidence: 55%
“…Males compete for position in a dominance hierarchy used to control access to estrus females (Le Boeuf, 1974;Haley et al, 1994) while fasting from food and water, losing~36% of their arrival body mass over a 3-month period Crocker et al, 2012). During this period, males have low rates of water flux and spare protein efficiently (Ortiz et al, 2006;Crocker et al, 2012). Studies in fasting and lactating female elephant seals have suggested reduced insulin response and sensitivity (Fowler et al, 2008;Viscarra et al, 2011aViscarra et al, , 2011b.…”
Section: Introductionmentioning
confidence: 99%